Smart speakers and customer experience in service contexts - Ruiz‐Equihua, D.; Romero, J.; Casaló, L. V.; Loureiro, S. M. C. (Psychology and Marketing, 2023)
The use of artificial intelligence-based devices, such as smart speakers, is rising in frontline services, as such devices can perform several tasks for customers. However, little is known about customer responses to interactions with smart speakers that occur during service encounters. This research encompasses three studies intended to enhance our currently scarce knowledge of how customers respond to interactions with smart speakers during service encounters. Focusing on the hospitality industry, the first study shows that smart speakers improve evaluations of the hotels that use them in terms of customer ratings and positive affects. The second study demonstrates that automated social presence and psychological ownership feelings are key mechanisms that explain the development of valuable customer responses. The third study, which uses virtual reality, suggests that better actual behaviors are exhibited by people who appreciate the incorporation of smart speakers into services. Thus, the findings indicate that smart speakers improve service experiences, especially if used to carry out hedonic tasks usually performed by employees.